Extraneural Metastases From a High-Grade Glioma (HGG) With an H3F3A G34R Mutation - Jethanandani, Amit; Gule-Monroe, Maria K.; Chen, Melissa; Johnson, Jason M. (Frontiers in Oncology, 2019)
Distant metastatic disease from gliomas is extremely rare. We report the case of a 17-year-old female​ with an H3F3A G34R mutated infiltrative glioma who developed painful osseous metastases to her pelvis and spine within three months of clinical presentation. The presence of an H3F3A mutation in these patients may indicate further work-up to include intensive staging examination.